2006
DOI: 10.1021/ja060186n
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Nitric Oxide with Tetrathiolato Iron(II) Complexes:  Relevance to the Reaction Pathways of Iron Nitrosyls in Sulfur-Rich Biological Coordination Environments

Abstract: The mechanism of formation of dinitrosyl iron complexes (DNICs) coordinated by cysteine residues at iron-sulfur protein sites has received little attention in the chemical literature. As a logical first step toward elucidating this mechanism and characterizing new iron-nitrosyl intermediates, we investigated the interaction of NO (g) and NO+ with iron-sulfur complexes chosen to mimic sulfur-rich iron sites in biology. The reaction of NO (g) with [Fe(StBu)4]2- cleanly affords the mononitrosyl complex, [Fe(StBu)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
111
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(123 citation statements)
references
References 27 publications
12
111
0
Order By: Relevance
“…Similar variations are also known for S = 3/2 nonheme {FeNO} 7 systems, most, but not all, of which exhibit bent nitrosyls with FeNO angles around 150° [4]. Thus, Harrop and Lippard have reported a pseudotetrahedral S = 3/2 {FeNO} 7 tristhiolate complex with an unusual linear FeNO unit [35]; We hope to present theoretical analyses of these systems, in collaboration with Professors Stephen Lippard (MIT) and Stephen Koch (SUNY, Stony Brook), within the foreseeable future.…”
supporting
confidence: 55%
“…Similar variations are also known for S = 3/2 nonheme {FeNO} 7 systems, most, but not all, of which exhibit bent nitrosyls with FeNO angles around 150° [4]. Thus, Harrop and Lippard have reported a pseudotetrahedral S = 3/2 {FeNO} 7 tristhiolate complex with an unusual linear FeNO unit [35]; We hope to present theoretical analyses of these systems, in collaboration with Professors Stephen Lippard (MIT) and Stephen Koch (SUNY, Stony Brook), within the foreseeable future.…”
supporting
confidence: 55%
“…The sample was sealed in a cell with Mylar windows and the experimental beam size was 3 mm(H) × 2 mm(V). The background subtraction and normalization of the XAS data, according to χ(k) = [μ(k) × μ 0 (i)]/Δμ 0 (0), were done by the AUTOBK program 16 , where μ(k) is the measured absorption coefficient, μ 0 (k) is the background, and Δμ 0 (0) is the edge jump. The wave number is defined as k = [2 m(E-E 0 )/(h/2π)] 1/2 , in which E, E 0 ,, h/2π and m are the photon energy, threshold energy, Planck constant, and mass of the electron, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…A related series of DNICs have been prepared and structurally characterized, which revealed that ligand electronic effects of the coordinated thiolate ligands may play a role in regulating the release of NO from such species [38]. Despite this progress, there remains a paucity of information about the mechanism of formation of DNICs and other nitrosyl derivatives, in particular, their genesis via the reaction of NO with iron complexes housed in an all sulfur coordination environment [41,42].…”
Section: Introductionmentioning
confidence: 99%